PELATIHAN PENGADMINISTRASIAN RIASEC SEBAGAI LAYANAN KARIER BAGI GURU BIMBINGAN DAN KONSELING - Muhammad Zulfikar; Muhammad Ferdiansyah; Rully Andi Yaksa; Zubaidah Zubaidah; Fitriana (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
School counselors are not yet adequately informed about career services, have limitations in career service methods, and lack the use of effective tools such as the RIASEC (Realistic, Investigative, Artistic, Social, Enterprising, and Conventional) Test. This, in turn, reduces the effectiveness of the services provided. The identification of students' interests and talents presents a significant challenge for school counselors. The preponderance of students electing majors or further studies that are not congruent with their aptitudes constitutes an additional problem. The methodology employed in this community service activity entailed training in the application and administration of the RIASEC test. This training was conducted through lectures and hands-on practice, and was attended by 11 teachers, including school counselors, subject teachers, and class advisors. The results of the hands-on exercise in the utilization and administration of the RIASEC test indicated that nine individuals exhibited a propensity for a social career personality, while two individuals demonstrated a proclivity for a conventional career personality. This finding suggests that the utilization and administration of the RIASEC test are not challenging, as the instrument is quite straightforward.